‘The Most Peaceful I Ever Felt Writing’: A Contemplative Approach to Essay Revision - Grace Wetzel (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Contemplative practices can scaffold deeper reading, listening, and insight not only with course texts, but also with students’ own texts.